A Portrait of Filipino Lovers: Aesthetic Normalisation of #Relationshipgoals on Instagram - Julius Cesar Rosales Pascual (International Journal of Asia Pacific Studies, 2026)
This study examines how Filipino lovers (FL) represent and negotiate romantic relationships on Instagram (IG) within an artificial intelligence (AI)-mediated platform environment. It aims to understand how platform affordances and user practices interact in shaping contemporary forms of digital intimacy and the aesthetic normalisation of #relationshipgoals. Using qualitative textual analysis, this study examines forty-seven publicly accessible IG contents. The analysis focuses on patterns of relational representation, affective expression, and platform-driven visibility to identify how romantic relationships are constructed and performed in everyday digital practice. Findings show that IG is not primarily used as a marker of relational authenticity, but as a curated space for managing visibility, emotional expression, and social validation. FL strategically engage the platform to negotiate jealousy and surveillance, establish social proof, construct emergent forms of romantic performance, respond to perceived relational threats, and express romantic excitement. These practices demonstrate how intimacy is continuously negotiated. This study further finds that IG’s AI-mediated features, including algorithmic curation, filtering tools, and content circulation systems, significantly shape how relationships are visually and emotionally represented. These platform mechanisms encourage selective disclosure and aesthetic enhancement, reinforcing emerging norms of idealised romantic visibility. This study concludes that romantic relational norms are co-produced through the interaction of algorithmic platform logics and culturally situated practices. This highlights how intimacy, visibility, and relational aesthetics are actively constructed in AI-mediated social media environments.